2018
DOI: 10.1002/adma.201704304
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks for Water Harvesting from Air

Abstract: Water harvesting from air in passive, adsorption-based devices holds great potential for delivering drinking water to arid regions of the world. This technology requires adsorbents that can be tailored for a maximum working capacity, temperature response, and the relative pressure range in which reversible adsorption occurs. In this respect, metal-organic frameworks (MOFs) are promising, owing to their structural diversity and the precision of their functionalization for adjusting both pore size and hydrophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
462
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 597 publications
(513 citation statements)
references
References 168 publications
(169 reference statements)
11
462
0
7
Order By: Relevance
“…[24] Consequently, harvesting water from air has emerged as another promising approach to address the water shortage issue, especially in the arid and landlocked regions. [24] Consequently, harvesting water from air has emerged as another promising approach to address the water shortage issue, especially in the arid and landlocked regions.…”
Section: Photothermal-assisted Water Harvesting From Airmentioning
confidence: 99%
See 2 more Smart Citations
“…[24] Consequently, harvesting water from air has emerged as another promising approach to address the water shortage issue, especially in the arid and landlocked regions. [24] Consequently, harvesting water from air has emerged as another promising approach to address the water shortage issue, especially in the arid and landlocked regions.…”
Section: Photothermal-assisted Water Harvesting From Airmentioning
confidence: 99%
“…[202,203] In this device, the water adsorbent layer was fabricated by infiltrating MOF-801 powders into porous copper foam, while the solar absorber side was coated with graphite or pyromark painting to ensure the MOF-801 with high temperature (i.e., 80 °C) to desorb water from. [24,[205][206][207] Recent report has demonstrated that optimized water uptake ability will be achieved if the pore diameter of MOFs is above the critical diameter of water capillary action. However, the separation of photothermal materials and MOF-801 brings a huge obstacle to utilize solar-driven heat to obtain the total release of absorbed water within the pores of MOF-801, because of low thermal utilization efficiency.…”
Section: Photothermal-assisted Water Harvesting From Airmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption isotherms of water vapor recorded near room temperature for MOFs offer important information about the hydrophobicity/hydrophilicity of their internal surfaces . There are six types of physisorption isotherms in the IUPAC recommendations updated in 2015 ( Figure a) .…”
Section: Assessment Of Hydrophobicity In Mofsmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), also called porous coordination polymers (PCPs), are a class of porous materials commonly obtained by the facile hydrothermal or solvothermal reactions of metal ions and bridging organic ligands at relatively low temperatures . In the past two decades, extensive research has been devoted to developing new MOFs and to exploring their application potential in many fields, such as gas storage, separation, catalysis, sensing, and biomedicine . Early on, a handful of MOFs was found to show a low affinity toward water and a permanent porosity, and this class of hydrophobic MOFs later received increasing attention due to their potential for use in practical adsorption and separation processes, even under humid conditions or in water.…”
Section: Introductionmentioning
confidence: 99%